Islamisation of Science: Al-Attas’ View and Its Implementation at Qur’anic Boarding School Darul Fattah Junior High School - Hidayat, Surya; Fikri, Alfian Izzul; Harsono, Iwan (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The Islamization of science was born because of the rapid development of Western science in the midst of the decline of Muslim science. So that many fields of science are adopted from Western understanding which tends to contain elements of secularism. In addition, the atomization of science that separates science and religion makes science further away from the concept of religion. To maintain the existence of Islamic science in this era, the Islamization of science was born as a solution, where this science combines the advantages of each without eliminating the sacredness of Islam in it. Syed Muhammad Naquib Al-Attas is one of the figures in the Islamization of Science. Purpose. The purpose of this research is to find out how the application of Islamization according to Al Attas’ view in schools. Method. this research used a qualitative approach. With the case study method, students who study at the Quran Darul Fattah Boarding School South Lampung. The data collection technique is observation. Data analysis in this study is through data collection, data presentation and drawing conclusions. Results. The result of this research is that the Islamization of science has been implemented in this school which is contained in the curriculum, learning materials, character building outside the classroom and the involvement of student guardians. Conclusion. The conclusion is that Islamization can be applied in schools and can be integrated with the existing system and in the daily lives of students in this school both related to subjects and norms inside and outside the classroom.